Surrogacy and Parenthood: A European Saga of Genetic Essentialism and Gender Discrimination - Levy, Mélanie (My University, 2022)
This paper tells a story of shifting normativities, from tradition to modernity and back, regarding the recognition of legal parenthood in non-traditional families created through crossborder surrogacy. The cross-border nature of the surrogacy is often forced as most domestic legal frameworks in Europe still restrict the creation of non-traditional families through assisted reproductive technologies. Once back home, these families struggle to have birth certificates recognized and establish legal parenthood. The disjuncture between social reality and domestic law creates a situation of legal limbo. In its recent case law, the European Court of Human Rights has pushed for domestic authorities to rectify this situation but, at the same time, has filled the legal limbo with genetic essentialism and allowed for gender discrimination when recognizing legal parenthood. While giving full effect to a genetic father’s foreign birth certificate based on identity and best interests arguments, the Court accepts that a genetic mother must adopt to establish a legal parent-child relationship. The paper critically addresses this intriguing imbalance. It deconstructs the Court’s genetic essentialism encouraging a biologically determined view of parenting, which sidelines the social (i.e., non-genetically related) parent and contradicts the purpose of assisted reproduction to overcome biological barriers. The paper concludes by rejecting the gender-discriminatory element of power and control over legal motherhood imposed by the procedural step of adoption.